Penerepan Akuntasi Sektor Publik, Ketidakpastian Lingkungan Kerja, Pengawasan Sistem Pengendalian Internal, Kualitas Laporan Keuangan, Kejelasan Sasaran Anggaran Terhadap Penerapan Transparansi Pelaporan Keuangan Pemerintah Daerah - Juniawan Mandala Putra; Martinelly Sembiring; Lasro Habeahan (Jurnal Doktor Manajemen (JDM), 2022)
This study aims to test the application of public sector accounting, work environment uncertainty, internal control system supervision, the quality of financial statements, clarity of budget targets on the implementation of government financial reporting transparency. Respondents in this research are government employees of Mayor of Central Jakarta, South Jakarta and West Jakarta, the number of government employees who are the sample of this study are 3 government offices of DKI Jakarta each government office 50 respondents government officials. Sampling method used in this study is a random sample, while the method of data processing used by the study is multiple regression analysis.The data is done through survey by using questionnaires distributed to respondents. The data analyzed by using multiple regression analysis supported by SPSS version 24.0 result of this research indicate that the influence of public sector accounting implementation, work environment uncertainty, internal control system supervision, quality of financial report, clarity of significant budget targets to the application of transparency of government financial reporting. The result of adjusted R square found that, the application of public sector accounting, work environment uncertainty, internal control system supervision, quality of financial report, clarity of budget target to the implementation of transparency of government financial reporting can be explained by 25,0% while 75,0% other variables not included in this research model.